VIOLATION OF MAXIM OF CONVERSATION IN BILL WATTERSON’S CALVIN AND HOBBES - Muladata, Aradeansyah Satria (Humaniora Scientia, 2018)
This research discusses violation of maxims of conversation in the strip comics entitled Calvin and Hobbes. The comic is a daily serial comic which tells about the main character named Calvin and his imagination tiger doll named Hobbes. The comic provides daily conversations among Calvin, Hobbes and people surrounding him. The research focuses on the kinds of violation of maxim of conversation and the purpose of the violation. Generally, this research is included in descriptive study. The steps in conducting the research are collecting, classifying, and analyzing the data. The entire data of this research are taken from the strip comics entitled Calvin and Hobbes July 1st 2014 to July 31st 2016 edition written by Bill Watterson. Then, the unit of analysis of this research is the whole conversations which represents violation of maxim of conversation. Furthermore, total sampling is applied to obtain the required data. Consequently, the data are analyzed one by one. To analyze the data, referential equivalent method is used to classify the kinds of violated maxim of conversation and pragmatic equivalent method is applied to reveal the purposes. Based on the analysis, the highest violation of maxim of conversation is the violation of maxim of relevance by 11 data. Furthermore, violation of maxim of quality and quantity are in the lowest position by 7 data only. Meanwhile, based on the purpose of the violation of maxims, representatives are the most frequent purpose of the violation by 15 data. Then, directives purpose is the smallest by only 3 data.